Impact of combined xylanase and β-glucanase enzymes on digesta transit time, short-chain fatty acids, and caecal thermal profile of broilers fed corn–soy-based diets - Pasquali, Guilherme A.M. [UNESP]; Dos Santos, Tatiane S. [UNESP]; Zanetti, Leonardo H. [UNESP]; Dornelas, Livia C. [UNESP]; Cruvinel, Jéssica M. [UNESP]; Muro, Everton M. [UNESP]; Araujo, Robert G.A.C. [UNESP]; Netto, Raimundo G.F. [UNESP]; Denadai, Juliana C. [UNESP]; Pezzato, Antonio C. [UNESP]; Sartori, José R. [UNESP] (Canadian Science Publishing, 2021)
A study was conducted to evaluate the effects of including a xylanase + β-glucanase enzyme product in corn–soy-based diets on performance, caecal short-chain fatty acids and thermal profile, ileal digestibility, and intestinal kinetics of broiler chickens. A total of 744 male day-old chicks were randomly allotted to 24 floor pens and distributed in a 2 × 2 factorial arrangement with low or standard energy level × without or with 100 g of the enzyme per ton of feed. Enzyme supplementation improved bodyweight gain from 1 to 21 d (P < 0.05). An increased caecal concentration of acetic acid was observed when the enzyme was added to the low-energy diet (P < 0.05). The pH of the caecal content was reduced (P < 0.01), and the caecal temperature was increased by low-energy diets (P < 0.05). The apparent ileal digestibility of energy was improved by the enzyme (P < 0.01). The addition of the enzyme increased the mean retention time in the distal ileum (P < 0.05). In summary, the addition of a xylanase + β-glucanase enzyme product in corn-based diets increases the retention time of digesta in the distal ileum and the caecal acetic acid concentration, improves ileal digestibility of energy and performance from 1 to 21 d in broiler chickens fed corn–soy-based diets.
Keywords: Carbohydrase; NSP enzymes; Thermography